Enhancing Waste Bank Efficiency Through a Web-Based Information System with Haversine Method Route Optimization - Asmunin; Kamaluddin Primajaya, Muhammad; Rohman Nudin, Salamun; Arwin Dermawan, Dodik; Zul Fahmi, Hafizhuddin (Proceeding of International Joint Conference on UNESA, 2024)
The Government of Mojokerto City is an enclave area within Mojokerto Regency, East Java Province, which has faced challenges in waste management. One effective solution is by utilizing a waste bank system. As a recent innovation, researchers have introduced Waste Bank, a concept of collection boxes for donating clothes and fabric scraps, in collaboration with the Department of Environment of Mojokerto City to manage textile waste. The process involves managing the outputs with Sewing house. The development of the Waste Bank management information system utilizes the Waterfall Method, with the Leaflet JavaScript Library for Open Street Maps visualization and the haversine method for finding nearby routes. Haversine is an effective algorithm for calculating distances between two points based on geographic coordinates on Earth’s surface, used to determine the distance between two points on the globe from longitude and latitude coordinates. The result of this research is the waste bank website application, which assists Mojokerto City residents in finding the nearest waste bank locations, monitoring the distribution of waste bank, and real-time navigation using Google Maps.